2015
DOI: 10.1002/adma.201504765
|View full text |Cite
|
Sign up to set email alerts
|

3D Graphene‐Foam–Reduced‐Graphene‐Oxide Hybrid Nested Hierarchical Networks for High‐Performance Li–S Batteries

Abstract: A 3D graphene-foam-reduced-graphene-oxide hybrid nested hierarchical network is synthesized to achieve high sulfur loading and content simultaneously, which solves the "double low" issues of Li-S batteries. The obtained Li-S cathodes show a high areal capacity two times larger than that of commercial lithium-ion batteries, and a good cycling performance comparable to those at low sulfur loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
280
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 512 publications
(281 citation statements)
references
References 46 publications
0
280
0
1
Order By: Relevance
“…Many efforts have been made to solve the shuttle effect that is to suppress the diffusion of LiPSs 3, 5, 6. Various carbon materials have been used as the sulfur host and conductive framework in Li–S batteries because of their high conductivity and large surface area 3, 6, 7. However, carbon materials always have a nonpolar surface, which leads to their relatively low affinity for polar LiPSs and does not help restrict LiPS shuttling.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been made to solve the shuttle effect that is to suppress the diffusion of LiPSs 3, 5, 6. Various carbon materials have been used as the sulfur host and conductive framework in Li–S batteries because of their high conductivity and large surface area 3, 6, 7. However, carbon materials always have a nonpolar surface, which leads to their relatively low affinity for polar LiPSs and does not help restrict LiPS shuttling.…”
Section: Introductionmentioning
confidence: 99%
“…Excellent cycling stability with up to 90% capacity retention was demonstrated by the electrodes, which is mainly attributed to the effectively reduced lithium polysulfide agglomeration due to the abundant pores of the dendrimers. Nevertheless, it should be noted that the reversible discharge capacity is around 600 mA h g −1 at 0.2 C. In other words, only an areal discharge capacity of around 2.4 mA h cm −2 can be delivered, which is even less than the state-of-theart Li-ion batteries (typically 4 mA h cm −2 ) [163,170]. A 7.2 mg cm −2 sulfur-loaded electrode with similar components was also obtained by using a modified polybenzimidazole (mPBI).…”
Section: A 2d Current Collector Design For High-loading Cathodesmentioning
confidence: 94%
“…However, they are still a long way from their practical application due to the following reasons. Firstly, the scaffolds of most cathodes are prepared via freeze-drying [88,170], filtration [43,186], chemical vapor deposition (CVD) [170,189], and electrostatic spinning methods [68]. The cost and large-scale reliability should be taken into consideration for industrial application.…”
Section: B 3d Current Collector Design For High-loading Cathodesmentioning
confidence: 99%
“…Graphene-based [142] films were used as such an interlayer and the cycling performance of the lithium-sulfur battery was greatly improved [125,126]. More recently, Liu et al reported a naphthalimide-functionalized poly(amidoamine) dendrimer and GO composite (Naph-Den-MGO) film, which combined chemical trapping and physical blocking and effectively suppressed LiPS shuttling [127].…”
Section: Graphene Papers or Membranesmentioning
confidence: 99%
“…As a typical example, Hu et al reported a highly conductive graphene foam nested with a rGO aerogel (GF-rGO), as a current collector to solve the "double low" issues of Li-S batteries. This 3D graphene hierarchical network enables both a high sulfur content of 83% and sulfur mass loading of 9.8 mg cm −2 in the cathode to deliver an ultrahigh areal capacity of 10.3 mAh cm −2 together with excellent cyclability [142].…”
Section: Graphene Monoliths With 3d Networkmentioning
confidence: 99%